DNA metabarcoding of insects and allies: an evaluation of primers and pipelines - Brandon-Mong, G.J.; Gan, H.M.; Sing, K.W.; Lee, P.S.; Lim, Phaik Eem; Wilson, J.J. (Cambridge University Press, 2015)
Metabarcoding, the coupling of DNA-based species identification and high-throughput sequencing, offers enormous promise for arthropod biodiversity studies but factors such as cost, speed and ease-of-use of bioinformatic pipelines, crucial for making the leapt from demonstration studies to a real-world application, have not yet been adequately addressed. Here, four published and one newly designed primer sets were tested across a diverse set of 80 arthropod species, representing 11 orders, to establish optimal protocols for Illumina-based metabarcoding of tropical Malaise trap samples. Two primer sets which showed the highest amplification success with individual specimen polymerase chain reaction (PCR, 98%) were used for bulk PCR and Illumina MiSeq sequencing. The sequencing outputs were subjected to both manual and simple metagenomics quality control and filtering pipelines. We obtained acceptable detection rates after bulk PCR and high-throughput sequencing (80-90% of input species) but analyses were complicated by putative heteroplasmic sequences and contamination. The manual pipeline produced similar or better outputs to the simple metagenomics pipeline (1.4 compared with 0.5 expected:unexpected Operational Taxonomic Units). Our study suggests that metabarcoding is slowly becoming as cheap, fast and easy as conventional DNA barcoding, and that Malaise trap metabarcoding may soon fulfill its potential, providing a thermometer for biodiversity.